1987
DOI: 10.1016/0009-2614(87)80336-6
|View full text |Cite
|
Sign up to set email alerts
|

The luminescence of Cs2NaSbCl6 AND Cs2NaSbBr6: a transition from a localized to a delocalized excited state

Abstract: The luminescences of CsZNaSbCl, and CsrNaSbBr, are reported. For Cs*NaSbBr, the luminescence properties are described in terms of a band model. For Cs,NaSbCl, the luminescence is interpreted in terms of isolated Sb'+ centres, comparable with CszNaMC16-Sb'+ (M = SC, Y, La). The radius of the Sb'+ ion is larger in the chloro-than in the_bromo-elpasohte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…It is shown that the four chemical parameters, coordination number, fractional covalence, bond volume polarizability, and presented charge, are factors influencing the positions of excitation bands of Sb 3+ ion in host lattices. In particular, the conclusion is to some extent consistent with the previous observations by Blasse et al . Covalence and coordination number are usually considered to be two main factors that influencing the energy levels of ns 2 ion in crystals.…”
Section: Theoretical Methodssupporting
confidence: 91%
See 4 more Smart Citations
“…It is shown that the four chemical parameters, coordination number, fractional covalence, bond volume polarizability, and presented charge, are factors influencing the positions of excitation bands of Sb 3+ ion in host lattices. In particular, the conclusion is to some extent consistent with the previous observations by Blasse et al . Covalence and coordination number are usually considered to be two main factors that influencing the energy levels of ns 2 ion in crystals.…”
Section: Theoretical Methodssupporting
confidence: 91%
“…From the previous work about the spectroscopy of Sb 3+ discussed above, it can be found that crystallographic structure, coordination number, and the charge compensation effect, can influence the luminescence of Sb 3+ ion in host lattices. However, there is still a lot of research needed in this area to understand the quantitative correlations between the host environment and the optical properties of Sb 3+ ion.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations